2019
DOI: 10.1159/000499435
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quantum Dot Skin Penetration in Porcine Skin: Effect of Age and Anatomical Site of Topical Application

Abstract: Background: Pig skin is a widely acknowledged surrogate for human skin for in vitro/ex vivo skin penetration studies with application for small molecules and nanosystems. We have investigated the influence of biological factors such as age and anatomical site on the penetration and distribution of nanoparticles (2.1 nm hydrophilic CdTe/CdS quantum dots: QDs) in adult pig skin (APS), weanling pig skin (WPS) and newborn pig skin (NBPS) at two different anatomical sites (ear and abdomen). Methods: QDs in saline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The permeation of RSV through the skin was also assessed by measuring the cumulative amount of RSV in the receptor phase, and calculating the steady state flux and lag-times. Due to the lack of availability of human skin, newborn pig skin was used as a previously validated human skin surrogate [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The permeation of RSV through the skin was also assessed by measuring the cumulative amount of RSV in the receptor phase, and calculating the steady state flux and lag-times. Due to the lack of availability of human skin, newborn pig skin was used as a previously validated human skin surrogate [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of availability of human skin, newborn pig skin was used as a previously validated human skin surrogate [ 42 , 43 ]. Full-thickness skin was obtained from newborn Yorkshire piglets that had died at or within 24 h of birth, as supplied by a local veterinary service.…”
Section: Methodsmentioning
confidence: 99%
“…Hair was removed using Veet™ hair removal cream applied for 10 min and then thoroughly removed. This method has been previously validated on piglet skin and shown no skin damage [ 43 ]. The skin surface was rinsed with phosphate-buffered saline solution at pH 7.4 (PBS), wrapped in aluminum foil, and stored in a polyethylene bag at −20 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Polymeric nanoparticles are composed of materials that are generally regarded as safe and efficacious (GRASE). A number of studies have shown that they do not penetrate intact stratum corneum but do accumulate on the skin furrows and hair follicles [42], depending on their properties that can provide sustained release by controlled dissolution, degradation or diffusion [43,44].…”
Section: Targeted Topical Delivery Of Retinoids: Strategies To Impmentioning
confidence: 99%